IMPLEMENTASI BALANCED SCORECARD DALAM PENYUSUNAN RENCANA STRATEGIS DI RUMAH SAKIT UMUM DAERAH WANGAYA KOTA DENPASAR - Purnama Dewi, Ni Putu Sintya; Sisdyani, Eka Ardhani; Dwija Putri, I G.A.M. Asri (E-Jurnal Akuntansi, 2017)
This study aims to formulate The Balanced Scorecard-based strategic plan to enhance mission achievement of Wangaya Public Hospital of Denpasar, as a public service agency. Data that are collected through interview, observation, and documentation, consist of primary and secondary data. The data then are analyzed using SWOT and performance indicator analysis to set the strategic plan, which is based on the four perspectives of Balanced Scorecard, namely: employee and organization capacity; internal service process; financial; and customer and stakeholders perspectives. The strategic plan covers period 2016-2020, focusing on quality and service efficiency improvement. It also provides a number of performance indicators and targets presented on a strategic map in each level of management which is aligned to the entity’s strategic map of the hospital through the technique of cascading.
Keywords: Balanced Scorecard; cascading Balanced Scorecard, strategic plan